Response on Syeda Amna Bukhari, et al. (J Pak Med Assoc. 72: 1909-1912, 2022) Comparison of exergaming and vestibular training on gaze stability, balance and gait performance of older adults: A single blind randomized control trial - Syeda Amna Bukhari; Misbah Ghous; Poshmal Butt; Sania Khawar Kiyani; Aroosa Tariq (Journal of the Pakistan Medical Association, 2023)
Thank you for such an interactive feedback, research flourish by these interactions. Following are the explanations of the queries raised on article, “Comparison of exergaming and vestibular training on gaze stability, balance, and gait performance of older adults: A single blind randomized control trial” The points are hereby enlisted: